Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s13018-022-03408-7
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence and machine learning on diagnosis and classification of hip fracture: systematic review

Abstract: Background In the emergency room, clinicians spend a lot of time and are exposed to mental stress. In addition, fracture classification is important for determining the surgical method and restoring the patient's mobility. Recently, with the help of computers using artificial intelligence (AI) or machine learning (ML), diagnosis and classification of hip fractures can be performed easily and quickly. The purpose of this systematic review is to search for studies that diagnose and classify for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
(105 reference statements)
0
7
0
Order By: Relevance
“…With the development of science and technology, ML is also being used in the field of medicine to improve patient outcomes and diagnostic accuracy[ 31 ]. Recently, ML has been widely used in the diagnosis, classification, identification and prognosis of hip fracture patients[ 32 - 34 ]. Promising results were obtained by Forssten et al [ 35 ], who used ML to predict 1-year mortality after hip fracture surgery, and by Galassi et al [ 36 ], who used ML to assess hip fracture risk.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of science and technology, ML is also being used in the field of medicine to improve patient outcomes and diagnostic accuracy[ 31 ]. Recently, ML has been widely used in the diagnosis, classification, identification and prognosis of hip fracture patients[ 32 - 34 ]. Promising results were obtained by Forssten et al [ 35 ], who used ML to predict 1-year mortality after hip fracture surgery, and by Galassi et al [ 36 ], who used ML to assess hip fracture risk.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it revealed that the addition of AI assistance can further increase the accuracy of fracture diagnosis. 39…”
Section: Computer-assisted Navigation For Shoulder Surgerymentioning
confidence: 99%
“…Finally, it revealed that the addition of AI assistance can further increase the accuracy of fracture diagnosis. 39 In shoulder disease, rotator cuff tear (RCT) is one of the most common shoulder injuries. When diagnosing RCT, skilled orthopedists visually interpret magnetic resonance imaging (MRI) data.…”
Section: Artificial Intelligence and Deep Learning: Diagnostic Modelmentioning
confidence: 99%
“…Employing an accurate automated detection model for hip fractures on radiographs can aid experts in saving time and resources. As a result, automated tools using machine learning and deep learning models have been increasingly studied in the literature 18 , 19 . Many studies have employed deep learning models trained over thousands of annotated radiographs and demonstrated high accuracy for potential clinical deployment 20 – 32 .…”
Section: Introductionmentioning
confidence: 99%